Study and reports on the VAT gap in the EU-28 member states: 2016 final report - Grzegorz Poniatowski; Mikhail Bonch-Osmolovskiy; Misha Belkindas (Center for Social and Economic Research (CASE), 2016)
The analysis serves as the Final Report for the DG TAXUD Project 2015/CC/131, "Study and Reports on the VAT Gap in the EU-28 Member States", which is a follow up to the reports published in 2013, 2014, and 2015. In this report, estimates of the VAT Gap and the Policy Gap for the year 2014 are presented, as well as revised estimates for the years 2010-2013 "due to the transmission" of Eurostat national accounts from the ESA95 to the ESA10. This update covers Croatia, which was not included in the previous updates. While it was hoped that the update would also cover Cyprus, it has not been possible due to incomplete national accounts data. The VAT Gap is a measure of VAT compliance and enforcement that provides an estimate of revenue loss due to fraud and evasion, tax avoidance, bankruptcies, financial insolvencies, as well as miscalculations. It is defined as the difference between the amount of VAT collected and the VAT Total Tax Liability (VTTL), which is expressed in the report in bothabsolute and relative terms. The VTTL is the theoretical tax liability according to tax law, and is estimated using a "top-down" approach.
Keywords: H24; H26; 330; consumption taxation; VAT; tax fraud; tax evasion; tax avoidance; tax gap; tax non-compliance; policy gap